Strength Properties of Saturated Sand-Structure Interface by Triaxial Test Method - LIU Shiao, LIAO Chencong, CHEN Jinjian, YE Guanlin, XIA Xiaohe (Editorial Office of Journal of Shanghai Jiao Tong University, 2021)
A novel test method for analyzing the influence of stress path and roughness of structure on the strength characteristics of saturated sand-structure interface by using triaxial apparatus is presented. By making a triaxial specimen with a slope structure with a certain inclination angle, the soil slides along the preset failure surface during the shearing process, and the slope surface roughness of the structure can be controlled and adjusted. A triaxial instrument is used to control the changes in axial pressure,confining pressure to achieve loading in different stress paths. The soil slides along the structure surface with a certain angle during shearing when preformed failure surface exists. The roughness of the structure can be controlled and adjusted. The triaxial apparatus is used to control the confining pressure change of the sample to realize loading under different drainage conditions and stress paths. To verify the effectiveness of the method, direct shear test and triaxial shear tests are carried out on the specimen composed of Fujian sand and steel structures with different roughness and different stress paths. The results show that at the beginning of sliding, the friction angle of the interface in the interfacial constant normal stress path is smaller than that in the conventional shear path. Under smooth conditions, the interface friction angle obtained by direct shear test is 30% to 40% lower than that obtained by triaxial test. Under rough conditions, the interface friction angle obtained by direct shear test is slightly smaller than that obtained by triaxial test, and closer to the friction angle in normal stress shear paths.